Pengembangan Sistem Informasi Tugas Akhir Berbasis Website - Adhitya Pratama, Yudhistira; Nababan, Adli Abdillah; Ade Maulana; Purwa Hasan Putra; Nababan, Arif Hamied (Jurnal Sistem Informasi dan Teknologi Jaringan, 2024)
The rapid development of information technology has brought many changes in the field of education, one of which is the use of web-based information systems to support the process of completing student's final projects. The final project is an essential component in higher education programs, but often faces various challenges, such as coordination between students and supervisors, document management, and scheduling of activities. To address these issues, this research aims to develop a web-based final project information system that can help students and supervisors manage and monitor the final project completion process effectively. This research uses the Waterfall system development method, which consists of the stages of requirement analysis, system design, implementation, testing, and maintenance. In the requirement analysis stage, the researchers identify and document the system requirements, including the main features, functionality flow, user interface, and constraints that must be met. Intensive and collaborative communication with users, namely supervisors and students, is crucial at this stage. By understanding the system requirements comprehensively, the researchers can design appropriate solutions that meet user expectations.